Pengaruh Dewan Komisaris Independen, Kepemilikan Manajerial, Kepemilikan Institusional, dan Kualitas Audit Terhadap Manajemen Pajak (Studi Kasus Pada Perusahaan Perbankan Yang Listing Di BEI Periode 2012-2015) - Wahyuni, Eka; Sulistyo, Sulistyo; Dianawati, Eris (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to determine the effect of the independent board of commissioners, managerial ownership, institutional ownership, and audit quality on tax management. The independent variables in this study are the board of independent commissioners, managerial ownership, institutional ownership, and audit quality while the dependent variable in this study is tax management measured by CETR (Cash Effective Tax Rate). This study uses a sample of 13 banking companies listed on the Indonesia Stock Exchange in the period 2012-2015 using purposive sampling. The data analysis method is multiple regression analysis. The results show that a simultaneous independent board of commissioners, managerial ownership, institutional ownership, and audit quality affect tax management. While partially the independent board of commissioners affects tax management, managerial ownership has an effect on tax management, institutional ownership has an effect on tax management, and audit quality has no effect on tax management